Evaluación de riesgos en las estaciones de compresión de gas natural comprimido - Ramírez Barbieri, Juan Carlos (2022)
This article aims to present the risks in operations in a compressed natural gas compression station, to which employees are exposed to accidents and occupational diseases. The natural gas loading process consists of filling a semi-trailer with compressed natural gas by using a high-pressure hose from a loading table connected to a semi-trailer, where the gas comes from the quality pipeline and is compressed by compressors. for natural gas. This study is descriptive, the most relevant risks in the compressed natural gas loading process were evaluated. The methodology that was implemented was based on the information collected from the company's workers (accidents that occurred, occupational medical examinations carried out, surveys or other records), classifying the types of risks existing in each task according to the job position, where we identified the hazard and assess the level of risk, determining the process where the most relevant risk occurs. In summary, the results show that the most exposed workforce to accidents or contracting an occupational disease are in the task of Entering the Compressor Bunker to verify pressure and temperature parameters that are exposed to high noise exposure with a 32% high physical risk level that occurs in the natural gas compression process, followed by the task Exit the semi-trailers that workers are exposed to moving units with a 20% high locative risk that occurs in the compressed natural gas loading process.